2010
DOI: 10.3168/jds.2009-2819
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with concentrations of select cytokine and acute phase proteins in dairy cows with naturally occurring clinical mastitis

Abstract: The objective of the current observational study was to determine the potential associations between cow factors, clinical mastitis (CM) etiology, and concentrations of select acute phase proteins and cytokines in milk from affected quarters of cows with CM. Cows with CM (n=197) were grouped based on systemic disease severity, milk culture result, parity, days in milk (DIM), previous CM occurrence, and season of the year when CM occurred. Concentrations of lipopolysaccharide-binding protein (LBP), haptoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
6
40
1
7
Order By: Relevance
“…uberis-induced mastitis; the lowest one in milk from cows with mastitis caused by S. aureus and CNS. Our findings correspond to the results reported by other authors (Hiss et al 2007, Wenz et al 2010, Pyörälä et al 2011. Hiss et al (2007), who studied the concentration of haptoglobin in milk from cows with subclinical mastitis, demonstrated that mean levels of this acute phase protein in milk infected with the major pathogens (E. coli, S. aureus) were higher than in cases of mastitis caused by minor pathogens (C. bovis, CNS).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…uberis-induced mastitis; the lowest one in milk from cows with mastitis caused by S. aureus and CNS. Our findings correspond to the results reported by other authors (Hiss et al 2007, Wenz et al 2010, Pyörälä et al 2011. Hiss et al (2007), who studied the concentration of haptoglobin in milk from cows with subclinical mastitis, demonstrated that mean levels of this acute phase protein in milk infected with the major pathogens (E. coli, S. aureus) were higher than in cases of mastitis caused by minor pathogens (C. bovis, CNS).…”
Section: Discussionsupporting
confidence: 83%
“…The highest concentration of haptoglobin was observed in milk from cows with E. coli -induced subclinical mastitis and the lowest one in CNS infections. According to Wenz et al (2010), the concentration of haptoglobin and lipopolysaccharides-binding protein (LBP) was higher in milk with Gram-negative bacteria compared to their concentrations in Gram-positive-infected milk. Likewise, Pyörälä et al (2011) observed the highest concentrations of haptoglobin and SAA in milk from cows with E. coli -induced mastitis and the lowest concentrations in milk from cows with CNS-induced mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of a pathogen at a specific time of year might explain a season effect on mastitis. Wenz et al (2010) also recently showed that season might have resulted in lower concentrations of many of the innate immune response proteins. Thus, the higher concentrations of many of the proteins during the winter months could be linked to enhanced immune function associated with season.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the higher concentrations of many of the proteins during the winter months could be linked to enhanced immune function associated with season. Improved neutrophil chemotaxis and lymphocyte proliferation may have resulted in an increased number of cytokine-producing leukocytes in the infected mammary gland (Wenz et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In animals suffering from this disorder, the levels of these proteins have been also measured in milk. Hp levels in milk in cows affected by clinical mastitis were higher in cows with moderate to severe versus mild systemic disease (Wenz et al, 2010). In a study carried out by Safi et al (2009) in Holstein cows from 7 different dairy farms the levels of Hp and amyloid A were measured in milk (AAM) and serum in order to evaluate the use and compare the accuracy of both APPs in these specimens for the diagnosis of subclinical mastitis based on bacterial culture results and with comparison with the California mastitis test (CMT) and somatic cell counts (SCC).…”
Section: Disease and Apps In Cattlementioning
confidence: 99%